The Relationship between Spiritual Health and Water Consumption among the Local Community of Gorgan - Esmaiil Eslami (پژوهشنامه مدیریت حوزه آبخیز)
Extended Abstract Background: As a public belief, religion has always played a fundamental role in the development and strengthening of social institutions. Since the creation of mankind, religion has not only acted as a personal guide but also as a measure for regulating social behaviors and has played an important role in various areas, including natural resource management. One of the interesting patterns in the relationship between religion and nature is the connection formed based on the significance and sanctity of water in religious teachings. In this context, water is introduced as a symbol of purity, innocence, and spiritual health. According to this pattern, spiritual health, which refers to a deep connection to religious and divine values, plays a key role in regulating religious, civic, and individual relationships. Despite the great importance of this topic, few studies have investigated the role of religious beliefs in the consumption of natural resources, especially in Islamic societies. This shortage of research is largely due to the cultural and social challenges associated with studying such topics, avoided by many researchers. In reality, people’s religious beliefs and attitudes are often naturally inspired by nature and its resources, among which water is one of the most vital elements of nature, playing a crucial role in the survival and life of humanity. Islam, particularly in its Qur'anic teachings, repeatedly emphasizes the importance of water conservation and careful use. The Holy Qur'an refers to water as the source of life and stresses the need to care for this divine blessing. Alongside these teachings, religious beliefs have always played a central role in shaping people's attitudes and behaviors. One such belief, which is recognized as part of religious practice, is the concept of spiritual health, which refers to an individual's deep connection with religious teachings that can guide them toward more responsible use of natural resources, including water. This connection is not only evident in religious and ritualistic behaviors but also influences everyday life aspects, such as social interactions and the use of natural resources. However, fewer studies have specifically examined the relationship between spiritual health and optimal water use, particularly in Islamic societies. Cultural and social complexities associated with studying such topics have always posed challenges, leading to limited research in this field. Considering the role of water and its connection to religious beliefs and spiritual health, the present study seeks to investigate the relationship between religious attitudes, income levels, and water consumption in the community of Gorgan. This study aims to answer the question: Is there a relationship between individuals' religious attitudes and their water consumption? Additionally, the study explores the influence of other variables, such as gender, income level, family size, and employment status, on water consumption.